Pengaruh Akuntabilitas, Transparansi dan Komitmen Organisasi terhadap Kinerja Pemerintah Daerah (Studi Empiris pada Organisasi Perangkat Daerah (OPD) Dinas Provinsi Jambi) - Ratih Rosita; Asrini Asrini (Universitas Batanghari, 2022)
This study aims to examine the effect of accountability, transparency, and organizational commitment both simultaneously and separately on the performance of local governments in the regional apparatus organization (OPD) of Jambi province. The population in this study was the Regional Apparatus Organization - Service, totaling 18 offices in Jambi Province. The sample chosen in this study consisted of 3 (three) people, including the OPD Head, OPD Financial Administration Officer, and OPD Treasurer, so that the total number of respondents was 54 people. Research data collection techniques by distributing questionnaires to research respondents. While the data analysis technique used in this study is multiple linear regression analysis. The results of the study found that simultaneously accountability, transparency, and organizational commitment had an effect on the performance of local governments in the regional apparatus organization (OPD) of Jambi Province. Partially the variables of transparency and organizational commitment have an effect on local government performance, while the accountability variable has no effect on local government performance.